DEVELOPMENT OF ONLINE STORES SINCE COVID-19 - Rozentāle, Arta; Stafecka, Līga; Nikolajeva, Anna (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2021)
The field of e-commerce became rapidly relevant already in 2019, when buyers, along with various prohibits to restrict the spread of Covid-19, switched to online shopping. The situation caused by Covid-19 demonstrated the benefits of e-commerce. During this time, e-commerce has grown and developed, and e-commerce now serves as a lifeline for many companies at a time when face-to-face sales were banned. During this time, more and more online stores have emerged, and more brands are fighting for the attention of consumers, thus consumers are forced to overtake online stores, including those who previously used only face-to-face shopping.